The Racketeer - Grisham, John; Jackson, J. D. (New York : Random House Audio, 2012)
When a federal judge and his secretary fail to appear for a scheduled trial and panicked clerks call for an FBI investigation, a harrowing murder case ensues and culminates in the imprisonment of a lawyer who imparts the story of who killed the judge and why.
Unabridged.
Compact discs.
Read by J.D. Jackson.
Keywords: Judges -- Fiction; Legal stories; Suspense fiction; Audiobooks